Marketing research of expectations of target audience of consumers of products with functional orientation - Нездолій, Андрій Олегович; Антюшко, Дмитро Петрович (Eastern-European Journal of Enterprise Technologies, 2015)
Market expectations of the target audience of consumers who are regularly exposed to high static and physical activity were investigated. In modern economic relations, the need for new approaches to ensuring the competitiveness of goods is fundamental to success in the market. One of the main conditions for the product success on the market is to study the specific needs, expectations and preferences of the target consumer segment, aimed at the maximum satisfaction of their interests. Marketing research plays a paramount role in the development and subsequent introduction of new products. The research results point to a wide range of consumers with positive attitudes to products with functional orientation, particularly sweets for preventing diseases of the musculoskeletal system. The results of focus-group interviews and their detailed analysis were taken as a basis for developing new products of functional purpose, including sweets for persons with prolonged static and physical activity and is the basis for ensuring their competitiveness in the consumer market.